2015
DOI: 10.1016/j.jagp.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and Amygdalar Local Structural Differences in Elderly Patients with Schizophrenia

Abstract: Objectives Morphological abnormalities have been reported for the hippocampi and amygdalae in young schizophrenia patients, but very little is known about the pattern of abnormalities in elderly schizophrenia patients. Here we investigated local structural differences in the hippocampi and amygdalae of elderly schizophrenia patients compared to healthy elderly subjects. We also related these differences to clinical symptom severity. Design 20 schizophrenia patients (mean age: 67.4±6.2 years, MMSE 22.8±4.4) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 51 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…as it is known to be involved in several relevant behaviours, such as anticipation and responses to rewards and aversive events which are known to be abnormal in schizophrenia (Chau et al 2004, Greer et al 2014. As these three structures share several efferent and afferent anatomical connections, it has been suggested that brain circuits involving these regions are impaired in schizophrenia (Moore et al 1999), which has been confirmed in a number of studies finding functional (Hall et al 2010) as well as volumetric alterations in these structures in schizophrenia (Lauer et al 161 2001, Prestia et al 2015, Kittel-Schneider et al 2015 Increasingly, it is being hypothesized that the brain deficit in schizophrenia is one of "dysconnectivity", i.e, either increased or decreased connectivity between regions (For a more detailed review, Please see chapter 1). As the hippocampus, amygdala and nucleus accumbens share several efferent and afferent anatomical connections, it has been suggested that brain circuits involving these regions are impaired in schizophrenia (For a review, see Grace, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…as it is known to be involved in several relevant behaviours, such as anticipation and responses to rewards and aversive events which are known to be abnormal in schizophrenia (Chau et al 2004, Greer et al 2014. As these three structures share several efferent and afferent anatomical connections, it has been suggested that brain circuits involving these regions are impaired in schizophrenia (Moore et al 1999), which has been confirmed in a number of studies finding functional (Hall et al 2010) as well as volumetric alterations in these structures in schizophrenia (Lauer et al 161 2001, Prestia et al 2015, Kittel-Schneider et al 2015 Increasingly, it is being hypothesized that the brain deficit in schizophrenia is one of "dysconnectivity", i.e, either increased or decreased connectivity between regions (For a more detailed review, Please see chapter 1). As the hippocampus, amygdala and nucleus accumbens share several efferent and afferent anatomical connections, it has been suggested that brain circuits involving these regions are impaired in schizophrenia (For a review, see Grace, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…In human, MRI images revealed that patients with neurological and/or psychiatric diseases, including Alzheimer's disease, schizophrenia and depression, have a smaller volume of hippocampi than those of control subjects (Francis et al, 2013;Guo et al, 2014;Heckers and Konradi, 2010;Prestia et al, 2014;Reif et al, 2006;Rizos et al, 2014). One possibility for those findings is that neurogenesis may be decreased in those patients.…”
Section: Fabps and Neurogenesismentioning
confidence: 99%
“…amygdala and OFC. To the best of our knowledge, structural abnormalities of the amygdala in individuals with pt-DD have not been specifically addressed, though alterations of amygdala have been frequently reported in patients with SZ [42][43][44][45][46][47], particularly in the context of facial affective processing [48,49]. The involvement of the amygdala in the processing of fear and threat is well-documented [50][51][52][53], but specific contributions of the amygdala to the development and persistence of delusions are still under debate [54].…”
Section: Discussionmentioning
confidence: 99%